A bottom-up role of information asymmetry: opening the black-box of firms' resource allocation mechanism. Issue 1 (1st December 2021) - Blouch, Riffat; Khan, Muhammad Majid; Shakeel, Wajid
Abstract : Purpose: Drawing on the concept of resource-based theory of the firm; the purpose of this study is to analyze the influence of firms' strategic approaches on the firm performance via indirect effect using a multilevel, bottom-up approach. Design/methodology/approach: Using the survey method, the present study obtains data from 104 diversified manufacturing firms and analyzes the bottom-up effect of firms' strategic approach on efficient resource allocation using Mplus. Findings: Given the prevailing conditions, the study found that the motive of most firms is growth rather than risk mitigation or collaboration in the manufacturing sector of Pakistan. Furthermore, the study found that the bottom-level employees' information asymmetry has a significant impact on the strategic resource allocation decision, which can lead to resource allocation inefficiency. Research limitations/implications: Despite making a unique contribution, the present study has few limitations requiring researchers' attention to in the forthcoming. These include a low amount of data, self-reporting technique and failure to include all the possible reason that could cause resource allocation inefficiency. Practical implications: The present research has potential applications for managers of the manufacturing industry. First, the study alerts managers about the challenges of resource allocation. At the same time, this study provides critical implication for managing bottom-level employees. Originality/value: The current study has made a sizable impression in the literature of resource-based theory of the firm by recommending a model that augments the theoretical foundation of strategic management of the firm. So, closely considering these insights would be helping for the firms for allocating resources efficiently in the manufacturing industry.